Design of low phase noise CMOS VCO using cross coupled topology with capacitor feedback. (August 2016) - Hsu, Meng-Ting; Li, Wei-Jhih; Hsu, Shuo-Chang
Abstract: In this paper, a new structure for a capacitor feedback with quality factor enhancement of 5 GHz band CMOS VCO is presented. The proposed VCO was able to reduce the parasitic effect of the circuit at high frequencies and without additional body biased voltage. The phase noise was improved with this capacitor feedback circuit. The circuit was analyzed by means of a simplified high frequency model. The improvement of low power consumption resulted from the adopted self-body biased technology without additional body biased voltage. The optimal low voltage design with 0.8 V was determined as the aim for low phase noise. The measured bandwidth of the frequency was from 5.07 GHz to 6.2 GHz with a 20.37% tuning ratio. The core consumption was 2.8 mW from the 0.8 V supply. The phase noise of the proposed VCO was −117.34 dBc/Hz at an offset frequency of 1 MHz. The figure of merit was −187.45 dBc/Hz and the figure of merit with tuning range (FOMT) was −193.6 dBc/Hz.